Hubungan Indeks Massa Tubuh (IMT) dan Rentang Gerak Articulatio Genus pada Wanita Dewasa di Jemaat Kalvari Kinaweruan - Injilia Lovely Momongan; Fransiska Lintong; Jimmy Rumampuk (Syntax Idea)
Body Mass Index (BMI) is associated with the range of motion (ROM); individuals with excess weight tend to have reduced ROM. The ROM value is an indicator of joint flexibility. Previous studies have shown that individuals with obesity exhibit a greater reduction in ROM compared to non-obese populations. This study aims to determine the relationship between BMI and the range of motion of the knee joint in adult women at Kalvari Kinaweruan Church. The research employed an observational analytic method with a cross-sectional design. Three instruments were used: a digital scale for body weight, a stature meter for height, and a goniometer for ROM measurement. The study sample consisted of 81 adult women from Kalvari Kinaweruan Church, selected using simple random sampling with a 5% margin of error based on Slovin's formula. Data were analyzed using Spearman correlation. Among the 81 respondents, Spearman correlation analysis revealed a significant negative relationship between BMI and knee extension (p < 0.001, r = 0.626) as well as knee flexion (p < 0.001, r = -0.616). There is a relationship between Body Mass Index (BMI) and the range of motion of the knee joint in adult women at Kalvari Kinaweruan Church.